A methods engineering study on AMI Semiconductor, Philippines Inc. - Batungbakal, Pia Marie; Gatpandan, Ana Carmela; Sarmiento, Rodeliza; Yap, Lisa Angela (College of Engineering, 2003)
The Methods Engineering study was conducted in AMI Semiconductor, Philippines, Inc., a wafer sorting and testing facility for Integrated Circuits. The study involved the analysis of the current operations with the aim of increasing productivity and reducing costs. The study focused on the company's Belgium operations in the Sort and Final Test Area. The group performed systems documentation and work measurement procedures prior to the identification of problems during plant visits. The major problems encountered by the group were : undetermined man-machine ratio, lack of a standardized procedure for loading and unloading, lack of a standard number of units loaded and unloaded, worker over fatigue due to excessive bending, walking and standing, quantification time too long and set up between cold and hot tests too long. For each of these problems, exploratory, recording and quantitative tools were used to evaluate and analyze the problems and to aid in the generation of recommendations and possible alternatives to the existing methods. Recommendations for the solution of the problems were generated, as well as the corresponding implementation plans for each. The group was able to determine the optimal ratio of operators to machines as 1:6 for Teradyne testers and 1:3 for TMT testers. The optimal number of units to be loaded and unloaded in order to minimize both machine and worker idle times was also determined to be 9 tubes and 7 cassettes for each loading and unloading cycle in the Teradyne and TMT testers respectively. Improvements in machine utilization, quantification procedure, standardization of loading and unloading, and working conditions were also provided. The proposed method, with a projection of 10 weeks for implementation, generated a total of Php4,130 for implementation costs but with a corresponding reduction in cycle time by as much as 78 minutes and net benefits of Php65700.00.